Glycerol in South African Table Wines: An Assessment of its Relationship to Wine Quality - Nieuwoudt, H.H.; Prior, B.A.; Pretorius, L.S.; Bauer, F.F. (South African Journal of Enology and Viticulture, 2017)
Glycerol is an important by-product of glycolysis and is quantitatively one of the major components of wine. While the physicochemical and sensory characteristics of pure glycerol are well established, the impact of varying levels of glycerol on general wine quality remains a topic of debate. Previous reports have relied on limited numbers of either commercial or experimental wines to assess the role of glycerol, leading to contradictory conclusions. Here we report on a large-scale assessment of the relationship between glycerol concentration and wine quality, based on the analysis of a significant number of commercial South African table wines of adjudged quality. The mean glycerol concentrations of 237 dry red (10.49 g/L), 158 dry white (6.82 g/L), 22 off-dry white (6.55 g/L), 16 special late harvest (8.26 g/L) and 14 noble late harvest wines (15.55 g/L) were found to be associated with considerable variation within each respective style. The final glycerol concentrations were significantly associated with the wine style (P<0.05). Shiraz wines had a mean glycerol concentration (10.22 g/L) which was significantly lower than that of Cabernet Sauvignon (10.81 g/L), Pinotage (10.46 g/L) and Merlot (10.62 g/L) wines (P<0.05). In both the dry white and off-dry white styles, the mean glycerol concentrations of Sauvignon blanc wines (6.31and5.42 g/L, respectively) were significantly lower (P<0.05) than those of the Chardonnay wines (7.08 and 7.03 g/L, respectively) and the Chenin blanc wines (6.81 and 6.85 g/L, respectively). No significant association between the final glycerol concentrations in commercial wines and the vintage, geographic origin or yeast strain used in inoculated fermentations could be established (P>0.05). The mean glycerol concentrations for South African dry red wines were significantly higher than those of dry white and off-dry white wines. Wine quality could not be significantly associated with glycerol concentrations in the dry red wines (P>0.05). For the dry white, off-dry white and late harvest wines this association was significant (P<0.05), although the exact nature of the association was somewhat different for the respective styles. Despite this positive statistical association, the observed differences between the mean glycerol concentrations of dry white and off-dry white wines of different quality ratings were too small to be of major practical value. The relationship between glycerol concentration and wine quality is reassessed on the basis of results obtained in this study as well as on recent reports in the literature.